Enhancing the Mastery of Basic Integer Operations Among Grade 8 Learners in Secondary Education Through MathSPARK - Ebio, Arvin; Buenaflor, Annie (Journal of Basic Education Research, 2025)
Purpose of the study: Mastery of basic integer operations, an essential foundational skill, enables learners to progress into complex mathematical concepts. Accordingly, this study investigates the effect of MathSPARK as an intervention material on learners’ mastery of this skill. Methodology: This study employed an explanatory-sequential mixed methods research design, which involved Grade 8 students from a public secondary school in Sorsogon City who met specific criteria. The data were collected through validated integer tests and a researcher-made questionnaire on student perceptions. The quantitative data were analyzed using both descriptive and inferential statistics, while the qualitative data were subjected to thematic analysis. Main Findings: The number of those who reached the “Mastered” and “Closely Approximating Mastery” levels increased, and those at the lower mastery levels were reduced. Statistical analysis of the results confirmed that the improvement in the learners’ mastery is significant; hence, MathSPARK is effective. Moreover, varied insights from the learners supported the findings, highlighting both the benefits and challenges they encountered. Novelty/Originality of this study: This study offers new insights into how to improve the mathematical skills of the learners by exploring the potential of available digital devices. It also provides an opportunity for a novel approach to enhance learning performance amidst challenges brought about by class disruptions and in an educational setting with limited resources, while taking advantage of what is available to learners